EVALUASI PELAKSANAAN PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA (PIS-PK) DAN PERAN PERAWAT DI PUSKESMAS CIPADUNG KOTA BANDUNG - EKI PRATIDINA; CUCU ROKAYAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
The Healthy Indonesia Program with a Family Approach (PIS-PK) is one of the government's goals to improve public health status in 2025 according to the 5th Nawa Cita agenda. The direction of health development according to RPJMN IV 2020-2024 aims to develop health efforts from curative moving towards preventive, promotive according to conditions. It needs to realize the vision of an independent community, living healthily. The Healthy Family Index (IKS) through the implementation of PIS-PK reflects the health conditions of families at the National, Provincial, Regency/City, District, sub-district, and family levels. Health problems based on Healthy Family Indicators are still in the Unhealthy Family category (IKS <0.500) and have not yet reached the National IKS target. The research aims to get an overview of the evaluation of the implementation of the Family Approach Healthy Indonesia Program (PIS-PK) and the role of nurses at the Cipadung Community Health Center, Bandung City. The research method is qualitative research with a descriptive approach. Data collection using in-depth interviews, and data analysis using content analysis. The results of the research at the preparation stage for the implementation of PIS-PK are that the number of human resources is still lacking, the budget cannot cover all needs, and the infrastructure is sufficient even though during the implementation of the tools there are errors. In the stage of the data collection process, there was resistance from the community during data collection, and health problem interventions were carried out based on the results of the PIS-PK data input, namely smoking, family planning, and ODGJ (People with Mental Disorders). In the evaluation stage, the process of inputting data into the PIS-PK application has not yet been wholly entered, the Healthy Family Index in both sub-districts is in the Unhealthy Family category (IKS <0.500), the role of health workers including nurses is still felt to be less than optimal. It is hoped that it will further optimize the role of family nurses in the community and improve health promotion media that are more appropriate to health problems. ABSTRAKProgram Indonesia Sehat Pendekatan Keluarga (PIS-PK) merupakan salah satu tujuan pemerintah untuk meningkatkan derajat kesehatan masyarakat tahun 2025 sesuai agenda ke-5 Nawa Cita. Arah pembangunan kesehatan sesuai RPJMN IV Tahun 2020-2024 mengarah pada pengembangan upaya kesehatan dari kuratif bergerak kearah preventif, promotif sesuai kondisi dan kebutuhan untuk mewujudkan visi masyarakat mandiri, hidup sehat. Indeks Keluarga Sehat (IKS) melalui pelaksanaan PIS-PK mencerminkan kondisi kesehatan keluarga di tingkat Nasional, Provinsi, Kabupaten/Kota, Kecamatan, Kelurahan sampai pada tingkat keluarga. Permasalahan kesehatan berdasarkan Indikator Keluarga Sehat masih masuk dalam kategori Keluarga Tidak Sehat (IKS <0,500) dan belum mencapai target IKS Nasional. Tujuan penelitian, mendapatkan gambaran evaluasi pelaksanaan Program Indonesia Sehat Pendekatan Keluarga (PIS-PK) dan peran perawat di Puskesmas Cipadung Kota Bandung. Metode penelitian, adalah penelitian kualitatif dengan pendekatan deskriptif. Pengumpulan data dengan indepth interview, analisis data menggunakan content analysis. Hasil penelitian pada tahap persiapan pelaksanaan PIS-PK jumlah SDM masih kurang, anggaran tidak semua dapat meng-cover kebutuhan, sarana prasarana telah mencukupi walaupun saat pelaksanaan alat ada yang eror. Tahap proses pelaksanaan pendataan, adanya penolakan dari masyarakat saat pendataan, intervensi masalah kesehatan dilakukan berdasarkan hasil input data PIS-PK yaitu masalah Merokok, KB, ODGJ (Orang Dengan Gangguan Jiwa). Tahap evaluasi, proses penginputan data ke aplikasi PIS-PK masih belum masuk seluruhnya, Indeks Keluarga Sehat pada kedua kelurahan masuk kategori Keluarga Tidak Sehat (IKS <0,500), peran tenaga kesehatan termasuk perawat masih dirasakan kurang optimal. Diharapkan lebih mengoptimalisasikan kembali peran perawat keluarga di komunitas dan meningkatkan media promosi kesehatan yang lebih tepat sesuai masalah kesehatan.